Menakar Aktualisasi Hak Partisipasi Anak melalui Pelibatan Anak dalam Law-Making Process Mitigasi Iklim - Azaria, Davilla Prawidya; Nasution, Ali Imran; Simanjuntak, Anni Alvionita; Puspitarini, Nabilah; Ferdianty, Shavina Putri (Wajah Hukum, 2025)
Children’s right of participation legitimized in national and international instruments. It is giving children right be hear, to express their views and opinios in matters affecting them significantly, such as the climate crisis. However, exercising this rights still faces various obstacles. This study will describe an analysis of restrictions on children's participation as obstacles to fulfilling children's rights in the law-making process to assuring child involvement can be implemented. As a normative research, this study will examine legal literature materials. The finding shows that children's participation in the policy-making process is faced with the assumption of adults who use age and maturity as benchmarks. This is not in line with the meaning in the Convention on the Rights of the Child which has legally provided legal certainty for children to have the right to participate and make decisions without limiting them solely by age. The Convention only states that children are given the right to participate with a weight that is appropriate for the child. Therefore, policy makers should be able to provide a broader interpretation to children so that these restrictions do not become obstacles. It is necessary to take into account the perspectives of children and uphold the best interests of the child premise to achieve intergenerational equity as a whole.